Keterampilan Berpikir Kritis pada Siswa Phlegmatis Menggunakan Video Pembelajaran - Sulistyowati, Fitria; Hartanti, Septi; Widodo, Sri Adi; Putrianti, Flora Grace (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2022)
This study is single-subject research with A-B-A design that aims to find out how to increase the critical thinking skills of a phlegmatic student in learning a system of linear equations with two variables with learning videos. The subject was a class VIII junior high school student with a phlegmatic personality who was selected based on observations and interviews with counseling teachers and school principals. Data collection techniques used are observation, tests, and documentation. Data were analyzed using analysis under conditions and between conditions. The result is mean level of critical thinking skills increased from 48.6 at first baseline to 74 at intervention and 91 at second baseline. These results are supported by the overlap percentage of 0%. This indicates that the learning videos affect increasing the critical thinking skills of the phlegmatic student in learning a system of linear equations with two variables. The results of this study are expected to be a reference in further research related to critical thinking skills in students with phlegmatic personalities.